Editwell : Final Cut Studio techniques from the pros - Jordan, Larry, 1950- (Peachpit Press, 2009)
Edit well: Final Cut Studio techniques from the pros is the book that in-the-trenches editors have been waiting for. It offers a holistic approach to using the tools in Final Cut Studio for those who are responsible for a variety of tasks beyond just straight editing.